1999
DOI: 10.1046/j.1432-1327.1999.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of Asp51 of Anabaena azollae glutamine synthetase.

Abstract: The role of Asp51 in the catalytic activity of glutamine synthetase from the cyanobacterium Anabaena azollae has been analyzed. Five mutant enzymes, D51S, D51A, D51E, D51N and D51R, were constructed by sitedirected mutagenesis and characterized. Asp51 appears to participate in the binding of ammonium ion, as affinity for this substrate was affected in all cases, although it varied according to the charge and/or size of the amino-acid residue, decreasing in the order Glu . Asn . Ser . Ala. The replacement of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…For site-directed mutagenesis of A. vinelandii GS encoded by the glnA gene, sequence alignments of GSs were carried out to identify a candidate amino acid in A. vinelandii GS that might display the critical function of D50 or D51 in ammonium binding and deprotonation as in E. coli (Liaw et al, 1995; or Anabaena azollae (Crespo et al, 1999) GSs, respectively. Thus the candidate D49 was identified for A. vinelandii GS.…”
Section: Isolation Of a Vinelandii Site-directed Mutants Of Glnamentioning
confidence: 99%
See 1 more Smart Citation
“…For site-directed mutagenesis of A. vinelandii GS encoded by the glnA gene, sequence alignments of GSs were carried out to identify a candidate amino acid in A. vinelandii GS that might display the critical function of D50 or D51 in ammonium binding and deprotonation as in E. coli (Liaw et al, 1995; or Anabaena azollae (Crespo et al, 1999) GSs, respectively. Thus the candidate D49 was identified for A. vinelandii GS.…”
Section: Isolation Of a Vinelandii Site-directed Mutants Of Glnamentioning
confidence: 99%
“…Previous work in E. coli and Salmonella typhimurium , and Anabaena azollae (Crespo et al, 1999) GS, showed that residues D50 or D51, respectively, are involved in ammonium binding and deprotonation at the active site of GS in these bacteria. Thus, by multiple sequence alignments we identified D49 in A. vinelandii GS as a candidate amino acid for a site-directed mutagenesis approach and obtained the A. vinelandii single mutant strain D49S, AV6 and double mutant strain ΔnifL-D49S, AV7 (Fig.…”
Section: Site Directed Mutagenesis Of a Vinelandii Gsmentioning
confidence: 99%